Developing assertiveness - Townend, Anni. (London : Routledge, 1991)
Self-awareness. Developing assertiveness in yoursejf. Developing and maintaining assertiveness in others.
Keywords: Psychology; Industrial; Psychology, Industrial; Industrial management -- Psychological aspects; Assertiveness (Psychology)